Status Of Solid Waste Management In The Municipality Of Jolo (Journal of Namibian Studies : History Politics Culture, 2023)
This study intends to determine status of solid waste management in the municipality of Jolo, Sulu during the Fiscal Year 2022. Employing descriptive-correlational research design with 112 respondents chosen through purposive sampling design, where data gathered through survey questionnaire and analyzed via weighted mean, standard deviation, t-test for independent samples, One-Way ANOVA, and Pearson’s r correlation coefficient, this reveals the following findings: 1) More than one-half of the respondents are female, married, within the 30-40 years old of age bracket, and great majority have bachelor’s degree. 2) Generally, residents of Jolo municipality affirmed that the status of solid waste management is affected by policy, facility, changing lifestyle, individual behavior, and community participation. 3) Profile variables used in this study such as gender, age, civil status, and educational attainment do not significantly intervene in ways how residents of Jolo municipality perceive the status of solid waste management. 4) All sub-categories subsumed under the status of solid waste management in Jolo municipality are moderately correlated. This study tends to support Kayode and Omole which states that composition of waste generation reflected variation of socio-economic factors of the people. Also, socioeconomic factors such as income, age, education, occupation and building types had greater influence on the choice of method of disposal. It this theory it was recommended that effective solid waste management can be achieved through the adoption of urban renewal strategy on the chaotic areas, provision of sizable fund by the government and proper education to the people among others.